Literature Review: Information System Audits as Instruments for Improving Governance and Service Quality in Public Organizations - Ginting, Lita Hepika; br Sembiring, Dini Sapira; Khairunnisa, Siti; Nasution, Fadilah; Wardhani, Neng Sri (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Information systems audit plays a strategic role in ensuring that information technology use in public organizations is effective, secure, and aligned with institutional objectives. The increasing adoption of information systems in the public service sector, including libraries, requires systematic evaluation mechanisms to control information technology risks and improve service quality. This study aims to examine the role of information systems audit in supporting information technology governance in public organizations by synthesizing findings from previous studies. This research employs a qualitative descriptive approach, drawing on a literature review. The results indicate that information systems audits, particularly those using the COBIT framework, are effective in identifying gaps in IT governance, enhancing accountability in information system management, and supporting continuous improvement of public service quality.